Home Blood Pressure Control After the Great East Japan Earthquake in Patients on Chronic Hemodialysis. Issue 2 (27th August 2013) - Tanaka, Kenichi; Nakayama, Masaaki; Kanno, Makoto; Kimura, Hiroshi; Watanabe, Kimio; Tani, Yoshihiro; Hayashi, Yoshimitsu; Asahi, Koichi; Suzuki, Kazuhiro; Watanabe, Tsuyoshi
Abstract At 14:46 on 11 March 2011, northeastern Japan was struck by a major earthquake measuring 9.0 on the Richter scale (the Great East Japan Earthquake). Several reports have suggested a transient blood pressure (BP) increase after a major earthquake, but its impact on BP in chronic dialysis patients has not been reported. In a retrospective review of 25 hemodialysis patients who were residents of Koriyama City, changes in the morning home BP after the earthquake were investigated. Home systolic and diastolic BPs were significantly elevated 1 week after the earthquake (158 ± 16 mm Hg vs. 151 ± 13 mm Hg, P < 0.01, for systolic; 81 ± 13 mm Hg vs. 78 ± 11 mm Hg, P = 0.01, for diastolic). Mean home BP 1 week after the earthquake was unchanged from baseline in patients treated with sympatholytics and/or renin‐angiotensin system (RAS) inhibitors. BP values returned to baseline by 4 weeks after the earthquake, but percent changes in mean BP were significantly greater even 2 weeks, 4 weeks, and 6 weeks after the earthquake in patients not treated with RAS inhibitors than in those treated with RAS inhibitors (2 weeks 7.0% ± 4.5% vs. 0.2% ± 5.0%, P < 0.01; 4 weeks 4.4% ± 5.9% vs. −1.8% ± 5.3%, P = 0.02; 6 weeks 4.6% ± 4.9% vs. −1.9% ± 3.9%, P < 0.01). On multiple regression analysis, RAS inhibitor use had an independent relationship with percentage increases in mean BP during the 6 weeks after the earthquake. Home BP was significantly increased after a major earthquake in patients on chronic hemodialysis. Prolonged deterioration of BP control after the earthquake was associated with non‐use of RAS inhibitors.